1981
DOI: 10.3109/17453678108991756
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of the Capitulum Humeri

Abstract: Fractures of the capitulum humeri are rare and the recommendations for treatment differ. Some authors recommend open reduction of the capitular fragment, while others advocate excising it. Twelve patients with anterior shearing fractures of the capitulum humeri were treated as inpatients in the Departments of Orthopaedic Surgery, Gothenburg, during the years 1973-1977. Ten patients, all treated with open reduction and internal fixation of the capitular fragment, were re-examined. The functional result was esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0
2

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 9 publications
2
20
0
2
Order By: Relevance
“…Mckee et al reported one patient of post-traumatic osteoarthritis in his series of six patients [4]. In a large series, Lansinger et al found no case of osteoarthritis of the elbow [22]. We also did not find osteoarthritis in any of our patients and believe that if reduction is anatomical with minimal damage to articular cartilage, post-traumatic osteoarthritis should not occur.…”
Section: Discussionmentioning
confidence: 43%
“…Mckee et al reported one patient of post-traumatic osteoarthritis in his series of six patients [4]. In a large series, Lansinger et al found no case of osteoarthritis of the elbow [22]. We also did not find osteoarthritis in any of our patients and believe that if reduction is anatomical with minimal damage to articular cartilage, post-traumatic osteoarthritis should not occur.…”
Section: Discussionmentioning
confidence: 43%
“…10 Even if osteonecrosis develops on radiographic assessment, function has been shown to be well maintained in previous series. 12 There are series that report conservative treatment with closed reduction techniques and immobilization. 20 It is now the perceived wisdom that surgery has reproducibly good outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…9,12 Loss of 30 of flexion is associated with a rapid loss of the effective reach of the arm. 1 The injury may also engender development of a contracture from scarring of the soft tissues, which will also adversely diminish the hand reach logarithmically.…”
mentioning
confidence: 99%
“…Despite its rarity, the prevalence of capitellar fractures is four times higher in women than in men, [10,31] and it has been suggested that this is due to the greater carrying angle in females along with weaker bones (osteoporosis). [11] These injuries mostly occur in young persons, and the female preponderance seen in the present series coincides well with the reported literature.…”
Section: Discussionmentioning
confidence: 99%